Analisis Pengaruh Kualitas Pelayanan dan Loyalitas Pelanggan terhadap Pendapatan Perusahaan pada PT JNE Express Kisaran Cabang Asahan - Fitri Handayani Sitorus; Saparuddin Siregar (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
Research in this journal to find out how the quality of srvice and customer loyalty affect revenue in jne companies in asahan, where expedition like this have grown and compete with each other to attract customer. The resarch method used is a type of qualitative descriptive research in wich data are taken from the results of quantifier and interviews. The result of this study is that the quality of service at a service company affects the company’s income, because if the company’s service quality is good and consumers are satisfied they will make loyal consumers to the company. The results showed a quite good value and the income of PT. JNE company in Cabang Asahan in the last three years has certainly be one of the suppliers of income for the company, this will provide a good impact for the company to be able to survive and compete with other service companies.